Association Between Proficiency and Efficiency in Electronic Health Records Among Pediatricians at a Major Academic Health System - Khairat, Saif; Zalla, Lauren; Gartland, Allie; Seashore, Carl (Frontiers in Digital Health, 2021)
Objective The purpose of this study was to evaluate the variations in EHR activity among General and Specialty pediatricians by investigating the time spent and documentation length, normalized for workload. Materials and Methods We conducted a cross-sectional study of pediatric physicians using Epic EHR at a major Southeastern academic healthcare system. We collected user-level EHR activity data of 104 pediatric physicians over 91 days from April 1st to June 30th, 2020. Results Of the 104 pediatrics physicians, 56 (54%) were general pediatricians and 48 (46%) were pediatric Specialists. General pediatricians spent an average of 17.6 minutes (IQR: 12.9-37) using the EHR per appointment, while Specialists spent 35.7 minutes (IQR: 28 – 48.4) per appointment. Significant negative associations were found between Proficiency scores and the amount of time spent in the system for Generalists (p-value<0.001). On the contrary, significant positive associations were found between Proficiency score and time in system for Specialists (p-value<0.01). Conclusion We report an association between EHR proficiency and efficiency levels among pediatricians within the same healthcare system, receiving the same EHR training, and using the same EHR system. The profound differences in EHR activity suggests higher priority should be given to redesigning EHR training methods to accommodate the learning needs of physicians.